Effects of supergene geochemical processes on desorption and bioavailability of polycyclic aromatic hydrocarbons in soil of karst area. Issue 1 (1st January 2021) - Xianjin, An; Wei, Li; Xinyue, Di; Baohua, Xiao
ABSTRACT: Supergene geochemical processes (SGPs) occur ubiquitously in the Earth´s surface, but their effects on the fate and bioavailability of polycyclic aromatic hydrocarbons (PAHs) in soil remain unclear. Study selected phenanthrene and pyrene as representative PAHs and yellow soil (YS) and limestone soil (LS) of karst area in southwest China, to investigate the effects of SGPs on the desorption and bioavailability of PAHs. Two soils were subjected to repeated freeze-thawing and long-term storage for SGPs. The hysteresis index values of pollutants increased with increase cycles of freeze-thawing and storage time. Under the SGPs, the phenanthrene fast desorption fraction of YS and LS decreased by 22.01% and 24.79%, respectively, and that of pyrene were by 23.81% and 28.12%, respectively. The desorption fraction of 24 hours was a better proxy of the fraction of bioavailability than that of 6 hours. The desorption rate of PAHs was negatively correlated with the hydrophobicity of PAHs.